Analysis and Design of Road Infrastructure: Geometric Design of the Subang-Ciasem Road - Agista, Shella; Surya, Mukhlis Ade; Hidayatullah, Syarif; Isradi, Muhammad; Indriany, Sylvia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The construction and improvement of road networks play an important role in supporting mobility, economic growth, and equitable regional development. The Subang-Ciasem corridor is a strategic route in Subang Regency that connects centers of economic activity, industry, and agricultural distribution to the northern coast road. This study aims to redesign the geometry of the Subang–Ciasem road to meet technical standards in accordance with the Procedures for Intercity Road Geometric Planning (Bina Marga, 2021) and the Indonesian Road Capacity Guidelines (PKJI, 2023). The design method was carried out by collecting existing data, including average daily traffic (ADT), soil conditions and CBR values, and geometric data. Slope and rainfall. The analysis results show that the road is classified as flat terrain with a design speed of 80 km/h and a final design life ADT of 7,470 vehicles per day. The design produced three main curves with a Spiral–Circle–Spiral (S–C–S) type, a minimum radius of 229 m, and a maximum superelevation value of 8%. The pavement design life is set at 12 years, with a composition of the HRS-WC layer and CTB 200 mm. LPA Class A, and LFA Class B. The analysis results yielded a safe geometric design. efficient and in accordance with technical standards. thereby improving traffic performance, comfort, and safety for road users in the Subang–Ciasem corridor and supporting regional economic growth.